2020
DOI: 10.3233/ajw200005
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Humus Content of Chernozems (Black Soils) and Soil Water Pollution Rate in the Pre-Ural Forest-Steppe of the Republic of Bashkortostan

Abstract: The current state of the anthropogenically transformed chernozems was monitored. The study was conducted in the forest-steppe of the Bashkir Pre-Urals. The monitoring has revealed worse soil fertility, which in turn negatively affects the environment, causing water pollution as a result of the anthropogenic transformation of black soils. The paper presents monitoring results of humus content in the chernozem (black soil) transformed under anthropogenic impacts for 1965-2016. The study data demonstrates that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Alkaline black soils affect rice production due to their high salt content. Shirale et al [27] found that planting dhaincha and sunhemp in sodic soils enhanced nutrient supply and showed potential to reclaim sodic soils [28]. In addition, fertilizer application methods and tillage practices also have a significant effect on soil nutrients.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Alkaline black soils affect rice production due to their high salt content. Shirale et al [27] found that planting dhaincha and sunhemp in sodic soils enhanced nutrient supply and showed potential to reclaim sodic soils [28]. In addition, fertilizer application methods and tillage practices also have a significant effect on soil nutrients.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%